2020
DOI: 10.1101/2020.10.29.360750
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Midbrain dopaminergic inputs gate amygdala intercalated cell clusters by distinct and cooperative mechanisms

Abstract: Dopaminergic signaling plays an important role in associative learning including fear and extinction learning. Dopaminergic midbrain neurons encode prediction error-like signals when threats differ from expectations. Within the amygdala, GABAergic intercalated cell (ITC) clusters receive the densest dopaminergic projections, but their physiological consequences are incompletely understood. ITCs are important for fear extinction, a function thought to be supported by activation of ventromedial cluster ITCs that… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 68 publications
(125 reference statements)
0
2
0
Order By: Relevance
“…The source of DA input to ITCs has largely remained elusive due to lack of molecular tools that can selectively target these neurons. However, recent studies suggest that DA input to ITCs originates from VTA/SN, similar to BLA (Ferrazzo et al, 2019;Aksoy-Aksel et al, 2021). D1, but not D2, receptors are abundantly expressed in the ITCs (Jacobsen et al, 2006).…”
Section: Intercalated Cells Of the Amygdalamentioning
confidence: 97%
See 1 more Smart Citation
“…The source of DA input to ITCs has largely remained elusive due to lack of molecular tools that can selectively target these neurons. However, recent studies suggest that DA input to ITCs originates from VTA/SN, similar to BLA (Ferrazzo et al, 2019;Aksoy-Aksel et al, 2021). D1, but not D2, receptors are abundantly expressed in the ITCs (Jacobsen et al, 2006).…”
Section: Intercalated Cells Of the Amygdalamentioning
confidence: 97%
“…However, different ITC clusters are connected and exert feedforward inhibition onto each other (Royer et al, 1999(Royer et al, , 2000Paré et al, 2003;Asede et al, 2015Asede et al, , 2021. Notably, a recent study demonstrated that lateral ITCs (l-ITCs) located in the external capsule send feedforward inhibition onto dm-ITCs and DA application reduces this inhibition onto dm-ITCs (Aksoy-Aksel et al, 2021). These findings suggest that DA likely inhibits l-ITCs, dampening the feedforward inhibition these neurons exert on BLA and dm-ITCs, and thus indirectly activates BLA 10.3389/fnbeh.2022.1041929 and dm-ITC neurons during aversive learning (Figure 1).…”
Section: Intercalated Cells Of the Amygdalamentioning
confidence: 99%